Revealing the strengthening contribution of stacking faults, dislocations and grain boundaries in severely deformed LPBF AlSi10Mg alloy - Snopiński, Przemysław; Kotoul, Michal; Petruška, Jindřich; Rusz, Stanislav; Żaba, Krzysztof; Hilšer, Ondřej (Scientific reports, 2023)
In this study, microstructural features direct metal laser melted (DMLM) aluminium-silicon-magnesium (AlSi10Mg) are investigated using advanced transmission electron microscopy (TEM) and high-resolution TEM (HRTEM). The focus is on post-processing by ECAP (Equal Channel Angular Pressing) and its effects on grain refinement, stacking fault formation and dislocation accumulation. In addition, the strength enhancing role of stacking faults is for the first time quantified. The results show that ECAP can increase the yield strength from 294 to 396 MPa, while the elongation increases from 2.4% to 6%. These results show that ECAP processing offers a new approach for producing AlSi10Mg products with improved strength and ductility.